To assess knowledge of cytotoxic spillage among pharmacy department staff in Selayang Hospital - Mohd Rashid, Siti Nurul Hidayah; Md Fadzil, Farah Shazwani; Sabri, Muhammad Syukri Azry (2010)
Cytotoxic drugs are used in the management of malignant diseases. They have been found to be carcinogenic, teratogenic and mutagenic. There is growing concern that the handling, preparation, administration and disposal of these substances may constitute an occupational hazard. Stavroula Theophanous and Elpidoforos S Soteriades (2008) believe that emergency procedures to cover spills or inadvertent release of hazardous drugs should be included in the overall health and safety programme of all oncology pharmacy. In order to deal with spillage is an emergency situation every hospital must have a written policy and provide appropriate training to its staff in advance, in order to reduce contamination of employees. Besides, spill kits should be available in all areas where cytotoxic drugs are prepared, dispensed, administered, transported, and disposed of. The objective is to recognize the knowledge level among them about spill kit and management strategies of cytotoxic spi 11. Study research was done by distributed to pharmacy department staffs to fill pre and post survey questionnaires in. Then, brochure acts as tool set to raise information and it was distributed to them. All data was analyses by using SPSS 13.0 and result show as difference percentage pre and post data. Thus, discussion was come out.